Cultural Encounters with the Arabian Nights in Nineteenth-Century Britain - Dickson, Melissa (Edinburgh University Press, 2022)
An overview of the cultural transmission of the Arabian Nights within nineteenth-century BritainFresh readings of canonical texts such as Charlotte Brontë's Jane Eyre, Charles Dickens's Hard Times and Lewis Carroll's Alice in WonderlandDiverse primary sources analysing the presence of the Arabian Nights in distinct areas of cultural production: constructions of childhood, archaeological and geological science, theatrical display, and exhibitionsAladdin, Sinbad, Ali Baba and the Forty Thieves, Scheherazade winding out her intricate tales to win her nightly stay of execution: the stories of the Arabian Nights are a familiar and much-loved part of the English literary inheritance. But how did these tales become so much a part of the British cultural landscape?Dickson identifies the nineteenth century as the beginning of the large-scale absorption of the Arabian Nights into British literature and culture. She explores how this period used the stories as a means of articulating its own experiences of a rapidly changing environment. She also argues for a view of these tales not as a depiction of otherness, but as a site of recognition and imaginative exchange between East and West, in a period when such common ground was rarely found
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Literary Studies; LITERARY CRITICISM / General; Popular culture and literature -- Great Britain -- History -- 19th century; Tales -- Arabian Peninsula